Towards a More Precise Understanding of Pseudo-Jonathan’s Origins - Goṭlib, Leor (Aramaic studies, 2021)
Abstract Many have assumed that Targum Pseudo-Jonathan (TgPsJ) is the product of first millennium Palestine. This study presents evidence suggesting that TgPsJ is neither from the first millennium, nor from Palestine. TgPsJ displays an unawareness of some basic facts with regard to the geography of the land of Israel, which makes the argument for its author being a native of Palestine unpersuasive. Excerpts from Even Bochan , a twelfth-century Hebrew lexicon written by Menachem ben Shelomo, the author of Sekhel Tov , exhibit textual similarities to statements found elsewhere only in TgPsJ. The nature of these statements lead to the conclusion that Even Bochan precedes TgPsJ and not vice versa. This suggests that the origins of TgPsJ are to be found in twelfth-century Italy.